Development of sulfur tolerant anode for solid oxide fuel cells - Bek, Yong Joo. (2009)
Fuel cells are energy conversion devices that operate by converting the chemical energy stored inside appropriate fuels into electrical energy. In particular, Solid Oxide Fuel Cells (SOFCs) are a type of fuel cell that has unique characteristics that make them outstanding candidates for use in future power generation systems. They have good fuel flexibility, provide high quality power and are relatively clean running when compared to traditional heat engines.